Cover Picture. Issue 4 (1st September 2022) - Unknown
Abstract : The cover image is based on the Review "Research progress on the relationship between intestinal microecology and intestinal bowel disease"(DOI: 10.1002/ame2.12262 ). It is currently known that as many as 10 14 microorganisms aggregate in the nutrient‐rich gut, which together constitutes the microbiota with very diverse characteristics. In this review, the authors summarize the currently available models of intestinal diseases caused by intestinal microbiota dysbiosis, and provide information on changes in the intestinal microbes after different therapeutic interventions, facilitating for select the corresponding animal models and treatment methods. Stable model of intestinal microbiota dysbiosis will further advance the comprehension of this disease and the development of targeted therapeutic approaches.